Moduli of surfaces with an anti-canonical cycle. (9th October 2014) - Gross, Mark; Hacking, Paul; Keel, Sean
Abstract: We prove a global Torelli theorem for pairs (Y, D) where Y is a smooth projective rational surface and D|-K_Y| is a cycle of rational curves, as conjectured by Friedman in 1984. In addition, we construct natural universal families for such pairs.